2017
DOI: 10.1007/s11136-017-1696-0
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life, developmental milestones, and self-esteem in young adults with bleeding disorders

Abstract: BackgroundThe treatment of bleeding disorders improved in the last decades. However, the effect of growing up with bleeding disorders on developmental, emotional, and social aspects is understudied. Therefore, this study assesses HRQOL, developmental milestones, and self-esteem in Dutch young adults (YA) with bleeding disorders compared to peers.MethodsNinety-five YA (18–30 years) with bleeding disorders (78 men; mean 24.7 years, SD 3.5) and 17 women (mean 25.1 years, SD 3.8) participated and completed the Ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 37 publications
0
32
1
Order By: Relevance
“…Longitudinal data collected with the KLIK method can provide insight into the causality of HRQOL outcomes over time. A recent study performed in young adults with CBD showed a lower HRQOL compared to healthy peers, suggesting that HRQOL decreases with increasing age in the transition period . Moreover, it would be interesting to add a disease‐specific HRQOL questionnaire to the KLIK website, for example the CHO‐KLAT, which has shown to have the best measurement properties .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Longitudinal data collected with the KLIK method can provide insight into the causality of HRQOL outcomes over time. A recent study performed in young adults with CBD showed a lower HRQOL compared to healthy peers, suggesting that HRQOL decreases with increasing age in the transition period . Moreover, it would be interesting to add a disease‐specific HRQOL questionnaire to the KLIK website, for example the CHO‐KLAT, which has shown to have the best measurement properties .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study performed in young adults with CBD showed a lower HRQOL compared to healthy peers, suggesting that HRQOL decreases with increasing age in the transition period. 43 Moreover, it would be interesting to add a disease-specific HRQOL questionnaire to the KLIK website, for example the CHO-KLAT, which has shown to have the best measurement properties. 44,45 This way, children and adolescents can be identified who are most likely to develop (haemophilia-related) problems in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…This enabled to start prophylactic treatment in patients with severe haemophilia (<1% clotting factor VIII or IX present in the blood) in order to prevent bleeding and joint damage, ultimately allowing patients to maintain a near normal lifestyle with little risk for arthropathy . Still, children and (young) adults growing up with coagulation disorders may experience impairments in daily life, such as restrictions in physical activity, travelling and school participation . Concerns exist about the long‐term impact of the disease and its treatment on adaptation and functioning in adult life.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal HRQOL and low employment rates found in a previous study have led us to conceive the current study, in which we aim to gain more in‐depth insight into professional functioning (paid employment, impairment in working) of YA with CCD and to assess whether sociodemographics, disease characteristics, functional disabilities, physical HRQOL and illness cognitions are associated with professional functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation